2014
DOI: 10.22146/ijc.21242
|View full text |Cite
|
Sign up to set email alerts
|

Major Anthocyanin Pigments in the <i>Ficus padana</i> Fruits: HPLC-DAD-ESI-MS Identification and Antioxidant Activity

Abstract: The anthocyanins in Ficus padana were extracted and identified by using high-performance liquid chromatography/diode array detection and electrospray ionization/mass spectrometry (HPLC-DAD-ESI-MS Keywords: Ficus padana; anthocyanin; HPLC-DAD-ESI-MS; antioxidant activity ABSTRAK Senyawa antosianin di dalam buah Ficus padana diekstraksi dan diidentifikasi dengan menggunakan kromatrografi cair kinerja tinggi diode array detektor dan spektrometer massa/elektron spray ionisasi (KCKT-DAD-ESI-SM). Antosianin dideteks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…3), are associated with the cinnamoyl groups (ring A) and benzoyl (ring C), respectively. 16,17 The theoretical analysis of C3G found that the main absorption peak is at 486.1 nm and is mainly affected by the H / L conguration, while the second theoretical peak is at 394.4 nm and is mainly affected by the HÀ2 / L conguration. As seen in Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…3), are associated with the cinnamoyl groups (ring A) and benzoyl (ring C), respectively. 16,17 The theoretical analysis of C3G found that the main absorption peak is at 486.1 nm and is mainly affected by the H / L conguration, while the second theoretical peak is at 394.4 nm and is mainly affected by the HÀ2 / L conguration. As seen in Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The characteristics of kemojo cake such as proximate analysis, calory, colour and sensory were determined by using Indonesian's National Analytical Method [16][17][18].…”
Section: Quality Analysismentioning
confidence: 99%
“…Two types of anthocyanin have been isolated from the figs, namely, pelargonidin 3-(6 00 -p-coumarylglucoside)-5-(4 000 -malonylglucoside) and pelargonidin 3-(6-00 -malonylglucoside) (Darwis et al 2014;Syukri et al 2014a, b). Pelargonidin 3-(6 00 -malonylglucoside) is the major component (91.4%) of the total anthocyanin in this species (Syukri et al 2014b). The pigment has the potential to be used as source of antioxidant and natural dyes (Darwis et al 2014;Syukri et al 2014b).…”
Section: Phyochemistrymentioning
confidence: 99%
“…Pelargonidin 3-(6 00 -malonylglucoside) is the major component (91.4%) of the total anthocyanin in this species (Syukri et al 2014b). The pigment has the potential to be used as source of antioxidant and natural dyes (Darwis et al 2014;Syukri et al 2014b). In addition, the chemical compounds extracted from the bark contains alkaloids, saponins, steroids, and tannins (Zulnely et al 2004).…”
Section: Phyochemistrymentioning
confidence: 99%